OPTIMASI PROSES INJEKSI DENGAN METODE TAGUCHI - Didik Wahjudi; Gan Shu San; Yohan Pramono (Institute of Research and Community Outreach, Petra Christian University, 2001)
At this time about 3% of products produced by